Bioremediation of chlorpyrifos-contaminated soil with biduri plant (Calotropis gigantea), bacteria, and biochar: Soil fertility impact - Rosariastuti, Retno; Mahdani, Sutheta Putra; Purwanto, Purwanto; Hartati, Sri; Sumani, Sumani (Brawijaya University, 2024)
During the Industrial Revolution, agriculture was linked to environmental issues. One issue is pesticide pollution. Bioremediation is needed because plant diseases and pests cause farmers to use pesticides excessively, polluting and decreasing soil production. This study evaluated soil fertility from bioremediation with biduri plants, bacteria, and biochar on chlorpyrifos-polluted shallot-growing soil in Brebes Regency. This type of research was an experiment in a greenhouse, using a factorial experimental design with a completely randomized design, consisting of two factors, namely bioremediation agent (A0: without bioremediation agent, A1: Atlantibacter hermannii, A2: bacterial consortium) and coconut shell biochar (B0: without biochar, B1: with biochar). There were six treatment combinations, then replicated three times for each treatment, so there were 18 treatment units. The data were statistically analyzed using ANOVA, Duncan Multiple Range Test, and Pearson correlation. The results showed that the best treatments that were able to improve soil fertility after bioremediation were treatments A1B0 (Atlantibacter hermannii + without biochar), A2B0 (bacterial consortium + without biochar), and A2B1 (bacterial consortium + with biochar). The A1B0 treatment (Atlantibacter hermannii + without biochar) increased the pH by 4.97%, and the soil available P was 12 times higher than the initial soil. The A2B0 (bacterial consortium + without biochar) treatment increased soil cation exchange capacity by 99.81% and soil organic C by 116% higher than the initial soil. The A2B1 (bacterial consortium + with biochar) treatment increased soil total N by 37.50% and available K by 38.47%, higher than the initial soil.